2020
DOI: 10.1017/dmp.2020.39
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Preparedness of Persons Requiring Special Care Ages 75 Years and Older Living in Areas at High Risk of Earthquake Disasters: A Cross-Sectional Study From the Pacific Coast Region of Western Japan

Abstract: Objective: The aims of this study were to examine the preparedness of vulnerable people ages 75 years and older and to clarify the characteristics of older adults that are associated with disaster preparedness. Methods: We conducted interviews with persons requiring special care ages 75 years and older living in coastal communities of western Japan, where earthquakes and tsunami disasters are a concern. The survey included participant characteristics such as demographic indicators, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Similarly, previous studies have shown that the knowledge disaster preparedness is more than 50% in China and Japan while conducting a household survey however, the observed knowledge level was much lower among Nepalese in our study [16,17]. We also identified that Nepalese do not participate in community drills and practice sessions probably because of the lower Japanese language skills that they mentioned as the perceived barrier to access the health information in Japan [18]. Nepalese immigrants residing in other English speaking countries like the United Kingdom, The United States, Canada, etc.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, previous studies have shown that the knowledge disaster preparedness is more than 50% in China and Japan while conducting a household survey however, the observed knowledge level was much lower among Nepalese in our study [16,17]. We also identified that Nepalese do not participate in community drills and practice sessions probably because of the lower Japanese language skills that they mentioned as the perceived barrier to access the health information in Japan [18]. Nepalese immigrants residing in other English speaking countries like the United Kingdom, The United States, Canada, etc.…”
Section: Discussionsupporting
confidence: 57%
“…However, this differs from that reported in Iran, where households with four or fewer members are associated with higher disaster preparation and social trust [ 41 ]. A study of a sample of older adults found that the composition of their households was not related to knowledge of evacuation routes [ 20 ]. This finding could be explained by the influence of family members as a social group so that the number of members in the household would involve sharing a greater amount of information about earthquake preparation through family discussions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, higher household income and education have been associated with good household preparedness for public health emergencies such as general disasters and infectious disease outbreaks [ 18 ]. In this sense, studies usually have a general approach to natural disaster prevention [ 5 , 11 , 17 , 18 ], while those that focus on earthquakes usually only describe variables such as sources of information, level of knowledge, attitudes, or perceptions [ 9 , 11 , 15 , 16 ], and some are even conducted on samples of parents, students, older adults, or health personnel [ 9 , 10 , 19 , 20 ]; therefore, there is still a lack of information about the culture of earthquake prevention in the general population and its associated factors. Our research question is the following: What are the frequency and factors associated with the knowledge of evacuation routes and having an emergency backpack?…”
Section: Introductionmentioning
confidence: 99%
“…Motoyoshi, Takao, and Ikeda (2008) reported that the intentions of local disaster prevention behaviors were higher with a greater awareness of the community, such as whether residents were committed to local autonomous activities or how much they interacted with people in their neighborhood. Hattori, Isowa, Hiramatsu, Kitagawa, and Tsujikawa (2020) found that close human interactions in the community facilitated disaster preparedness.…”
Section: Factors Affecting Disaster Prevention Awareness Among Residents Of Mountainous Areasmentioning
confidence: 99%